PERAN CREDIT UNION DALAM BIDANG AGRIBISNIS UNTUK PEMBANGUNAN PERTANIAN DAN EKONOMI - Beni, Sabinus; Manggu, Blasius (Jurnal Pendidikan Ekonomi (JURKAMI), 2017)
Abstract: Credit Union in its development does not merely serve members in the process of savings and loan members but related to member empowerment, especially in the field of agriculture. This research was conducted in Bengkayang Regency, West Kalimantan Province to see the real role of Credit Union in agriculture. The results showed that the role of credit union is still very small in the field of Agribusiness in Bengkayang Regency where from the total population of Bengkayang district, only 30.02% of Bengkayang district residents are members of credit union or 37,183 from 123,874 people. The data is still not accurate, given the public's habits to become a credit union member of more than one or several credit unions.Keywords: Agribusiness, Credit Union, Agricultural DevelopmentAbstrak: Credit Union dalam perkembangannya tidak sekedar melayani anggota dalam proses transaksi simpan pinjam anggota tetapi menyangkut pada pemberdayaan anggota terutama dibidang pertanian. Penelitian ini dilakukan di Kabupaten Bengkayang Provinsi Kalimantan Barat untuk melihat peran nyata Credit Union dalam bidang pertanian. Hasil penelitian menunjukkan bahwa peran credit union masih sangat kecil dalam bidang Agribisnis di Kabupaten Bengkayang dimana dari total penduduk kabupaten Bengkayang, baru 30,02% penduduk kabupaten Bengkayang yang menjadi anggota credit union atau 37.183 dari 123.874 jiwa. Data tersebut masih belum akurat, mengingat kebiasaan masyarakat untuk menjadi anggota credit union lebih dari satu atau beberapa credit union.Kata Kunci: Agribisnis, Credit Union, Pembangunan Pertanian